Comparison of the efficacy and safety of Rituximab (Mabthera™) and its biosimilar (Reditux™) in diffuse large B-cell lymphoma patients treated with chemo-immunotherapy: A retrospective analysis - Partha Sarathi Roy; Shiji John; Sadashiv Karankal; Sadhana Kannan; Preeti Pawaskar; Jayanta Gawande; Bhausaheb Bagal; Navin Khattry; Manju Sengar; Hari Menon; Sumeet Gujral; Reena Nair (Indian Journal of Medical and Paediatric Oncology)
Background: Rituximab (Mabthera™) have been in use in India since 2000. A biosimilar molecule of rituximab (Reditux™) was approved in India in 2007. This retrospective audit was done to compare the efficacy and safety of Mabthera™ with Reditux™. Materials and Methods: We reviewed the charts of 223 adult diffuse large B-cell lymphoma patients who had received cyclophosphamide, doxorubicin, vincristine and prednisolone with rituximab chemotherapy. Tumor recurrence, survival and toxicities experienced during chemotherapy were obtained from the patient charts. The survival analysis was restricted to patients who received at least 4 cycles of the same brand. Results: Of the 223 patients evaluated, 101 received Mabthera™, 72 received Reditux™. There were no differences in the infusional reaction rates, grades 3 and 4 neutropenia and oral mucositis between the two brands. Complete-remission (CR) rates were similar with Mabthera™ and Reditux™ (75% and 82%, respectively; P = 0.294). The progression free survival (PFS) rate at 5 years were 72% in Mabthera™ and 81% in Reditux™ (P = 0.382). The overall survival (OS) at 5 years were comparable in the two groups (66% in Mabthera™ and 76% in Reditux™; P = 0.264). Conclusion: We observed no significant differences in the toxicity, tumor response rates, PFS and OS between the two available brands of rituximab.